The Influence Of Motivation And Work Environment On Employee Performance In The Food Security Service Of South Lampung District - Catur Martalia; Mustakim , Senen (Jurnal Ekonomi, Manajemen, Akuntansi, 2025)
The South Lampung Regency Food Security Service has a very important role in ensuring the availability, accessibility and quality of food for the community. As one of the government agencies responsible for food security, the performance of employees in this department is a key factor in achieving organizational goals. To improve employee performance, two main factors that need to be considered are motivation and work environment. Work motivation is an internal and external drive that influences employee enthusiasm and desire to achieve certain goals. Apart from motivation, the work environment also plays an important role in influencing employee performance. A comfortable, safe and supportive work environment can increase employee job satisfaction and productivity. Factors such as physical facilities, relationships between employees, and good working conditions greatly influence work effectiveness and efficiency The aim of this research is to determine: 1. The influence of work motivation on employee performance 2. The influence of the work environment on employee performance 3. The influence of work motivation and the work environment together on employee performance at the South Lampung Regency Food Security Service. This research uses a quantitative descriptive research method, namely a research method that uses data in the form of numbers to analyze the facts found which aims to determine the relationship between variables in a population. The analysis used is simple and multiple regression. This research used 40 respondents. Based on the results of data analysis, the hypothesis answer was found as follows; There is an influence of work motivation (X1) on employee performance (Y) at the South Lampung Regency Food Security Service, with an influence level (R-square) of 70.8%. There is an influence of the work environment on employee performance at the South Lampung Regency Food Security Service with an influence level of 62.8%. There is an influence of work motivation and work environment together on employee performance at the South Lampung Regency Food Security Service, with an influence level of 76%..